2020
DOI: 10.1007/s11606-019-05525-2
|View full text |Cite
|
Sign up to set email alerts
|

Can Patient–Provider Interpersonal Interventions Achieve the Quadruple Aim of Healthcare? A Systematic Review

Abstract: BACKGROUND: Human connection is at the heart of medical care, but questions remain as to the effectiveness of interpersonal interventions. The purpose of this review was to characterize the associations between patientprovider interpersonal interventions and the quadruple aim outcomes (population health, patient experience, cost, and provider experience). METHODS: We sourced data from PubMed, EMBASE, and PsycInfo (January 1997-August 2017). Selected studies included randomized controlled trials and controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 89 publications
0
62
0
Order By: Relevance
“…Ultimately, most providers supported a hybrid model for telemedicine and in-office appointments; this would preserve the opportunity for face-to-face contact when needed for optimal decision-making and foster patient connection and flexibility, both of which influence physician burnout. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, most providers supported a hybrid model for telemedicine and in-office appointments; this would preserve the opportunity for face-to-face contact when needed for optimal decision-making and foster patient connection and flexibility, both of which influence physician burnout. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In doing so, the review revealed that interpersonal communication interventions with lower demands on provider time and effort were often as effective as those with higher demands. 22…”
Section: Resultsmentioning
confidence: 99%
“…21 The studies were a subset of articles from a systematic review that was conducted for a previous evidence synthesis project. 22 For this review, we focused on studies of physician communication skills interventions to facilitate comparison of implementation factors across similar types of interventions. For this proof-of-concept systematic review, our objective was to determine whether implementation factors could be reliably abstracted using the above guidelines.…”
Section: Systematic Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speculatively, one well-designed and evidence-based intervention that was implemented uniformly in a health service would have a more signi cant impact than multiple interventions implemented in different departments. This study contributes to the body of literature on the e cacy of single versus multiple interventions (44,45), where the evidence on the e cacy is caveat by the context and nature of the intervention. Nevertheless, in the context of the Victorian public inpatient services, using one evidence-based intervention in the areas at the point of care mentioned above is associated with improvement in overall patient experience.…”
Section: Discussionmentioning
confidence: 96%